Methodology for preliminary seismic design of extended pile-shafts for bridge structures. - Song, S. T. (Earthquake engineering & structural dynamics.)
Seismic design of extended pile-shafts requires a careful consideration of the influence of the surrounding soil on the overall response of the soil?pile system. In this paper, a procedure that incorporates soil properties into the process is developed for preliminary seismic design of extended pile-shafts. The method follows the well-accepted approach of using a force reduction factor to determine the lateral strength of the structure. The procedure involves an iterative process to arrive at the required amount of longitudinal reinforcement. Other outcomes of the procedure include the appropriate lateral stiffness and strength, as well as an estimation of the local curvature demand and ultimate drift ratio that can be used to ensure a satisfactory lateral response. The design procedure is capable of providing reliable results for a practical range of structural and soil properties. The versatility of the procedure is illustrated using two numerical examples of extended pile-shafts constructed in different soil sites.